The role of small-scale agriculture in Romanian context - Monica Miheala Tudor (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
In the last quarter of century (post-communist period after '89) in Romania, rural areas and small rural households were highly stable systems, providing social and economic security. Small-scale agriculture has become and continues to be the main supplier in rural labour market in the absence of other non-agricultural employment opportunities; achieve higher levels of economic performance compared to large farms by diversifying their production structure due to they have an important contribution to the national food security; food self-consumption, supported by small farms has an leverage effect against poverty. If the resilience means the ability of an individual, household, community, region or country to resist, to adapt, and quickly recover after a crisis, shock, change, the economic and social functions and roles assumed in the transition period by small Romanian rural households gives them the attributes of an resilient answer of the entire Romania to the post-communist changes and shocks.
Keywords: 330; rural areas; socio-economic changes; small agriculture; resilience; Romania